Meningkatkan Mutu Pendidikan Agama Islam melalui Implementasi Behaviour Modification Approach - Partono, Partono; Syarofi, Mochammad Zaimus (Tapis: Jurnal Penelitian Ilmiah, 2023)
The purpose of this study was to determine the Implementation of the Behavior Modification Approach to Improve the Quality of Islamic Religious Education at SDN 01 Padurenan Gebog Kudus. This research uses a qualitative approach and the type of research is field research, aiming to look at social phenomena or social facts associated with a theory related to these symptoms or facts. The subject of this research is PAI teachers. Data collection techniques used in the form of observation, interviews, and documentation. Testing the validity of the data used is in the form of source triangulation, technical triangulation, and time triangulation. Data analysis techniques use the Miles and Huberman models, which include Data Display, Reduction, and Data Verification Conclucion (Verification Drawing). The implementation of the Behavior Modification Approach in Improving the Quality of Islamic Religious Education has been quite successful because of an approach from stimulus to response through behavior change and careful preparation. This success is inseparable from the theory created by Thorndike in the form of Connectionism theory, this theory explains that by including the existence of a special interaction between stimulus and response, which influences behavior in the learning process. This influence can be applied through the laws of learning created by Thorndike, namely (1) the law of readiness, (2) the law of practice, (3) the law of consequences.